Hyperspectral Image Classification Using Reduced Extreme Learning Machine - Sigirci, Ibrahim Onur; Bilgin, Gokhan (IEEE, 2018)
In the classification of hyperspectral images, kernel based approaches have been shown to be successful results. Too much training or testing data in the images increases the computation time and memory requirements in the kernel computations. Extreme learning machines that can be used with the kernel approach also need the same requirements in kernel computations. In this study, improvements were made in terms of computation time and memory using reduced kernel extreme learning machines (RKELM). The obtained results are presented comparatively through the tables of performance and time information with kernel extreme learning machine (KELM).
Keywords: Hyperspectral images; classification; reduced kernel extreme learning machine; spectral information; REMOTE-SENSING IMAGES; Computer Science; Engineering